Bio-oil Upgrading via High-Pressure Reactive Distillation - Wang, Hongqi (Curtin University, 2020)
This study aims to investigate the roles of process parameters especially pressure and the major components in the high-pressure reactive distillation of bio-oil. The bio-oil distillation fraction yields and properties were evaluated to demonstrate the advantages of the distillation at elevated pressures over distillation at atmospheric pressure. The results indicate that high-pressure distillation can achieve high distillate yields with reduced polymerisation because high pressure can retain water and other light components in the liquid phase.